2016
DOI: 10.1177/0301006616643675
|View full text |Cite
|
Sign up to set email alerts
|

Low Vocal Pitch Preference Drives First Impressions Irrespective of Context in Male Voices but Not in Female Voices

Abstract: Vocal pitch has been found to influence judgments of perceived trustworthiness and dominance from a novel voice. However, the majority of findings arise from using only male voices and in context-specific scenarios. In two experiments, we first explore the influence of average vocal pitch on first-impression judgments of perceived trustworthiness and dominance, before establishing the existence of an overall preference for high or low pitch across genders. In Experiment 1, pairs of high-and low-pitched tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 57 publications
6
44
4
Order By: Relevance
“…Several acoustic features influence the perception of how trustworthy and cooperative the speaker is (Belin et al, 2017;Knowles & Little, 2016;Montano et al, 2017;O'Connor & Barclay, 2017;Oleszkiewicz et al, 2017;Ponsot et al, 2018;Tigue et al, 2012;Tsantani et al, 2016). Their influence could stem from the pleiotropic effect of testosterone on both acoustic features and cooperative behaviours (O'Connor & Barclay, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several acoustic features influence the perception of how trustworthy and cooperative the speaker is (Belin et al, 2017;Knowles & Little, 2016;Montano et al, 2017;O'Connor & Barclay, 2017;Oleszkiewicz et al, 2017;Ponsot et al, 2018;Tigue et al, 2012;Tsantani et al, 2016). Their influence could stem from the pleiotropic effect of testosterone on both acoustic features and cooperative behaviours (O'Connor & Barclay, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both acoustic features influence perception of how trustworthy a speaker is. For example, lower-pitched male voices and voices with high pitch variations are perceived as more trustworthy in general (Belin et al, 2017;Oleszkiewicz et al, 2017;Schirmer et al, 2019;Tsantani et al, 2016) or when trust is linked to the political context (Klofstad et al, 2015(Klofstad et al, , 2012Tigue et al, 2012). It remains unknown, however, whether these acoustic features correlate with actual trustworthiness, and not only with perceived trustworthiness.…”
Section: Discussionmentioning
confidence: 99%
“…Listeners judged each voice independently using a Likert scale (following, e.g., Feinberg, Jones, Little, Burt, & Perrett, 2005; Pisanski & Rendall, 2011). Although some previous studies have used a two-alternative forced-choice rating paradigm (e.g., Jones, Feinberg, DeBruine, Little, & Vukovic, 2010; Tsantani et al, 2016) or a scale/forced-choice hybrid (e.g., Vukovic et al, 2011), a Likert scale allows for more variance in listeners’ responses than does a binary task, and therefore may increase the likelihood of uncovering potentially subtle group differences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although trustworthiness has often been discussed as an element of warmth (Fiske et al, 2007), it remains unknown whether voice pitch affects judgments of warmth and trustworthiness in the same way. Indeed, studies with sighted listeners have indicated that speakers with low voice pitch are typically perceived as being more competent and trustworthy than speakers with higher voice pitch (Klofstad, Anderson, & Nowicki, 2015; McAleer, Todorov, & Belin, 2014; Tigue, Borak, O’Connor, Schandl, & Feinberg, 2012; Tsantani, Belin, Paterson, & McAleer, 2016). In contrast, studies examining voice-based assessments of warmth have produced equivocal results (Berry, 1991; Hughes, Pastizzo, & Gallup, 2008; Ko, Judd, & Stapel, 2009; McAleer et al, 2014).…”
Section: Voice-based Assessments Of Social Traitsmentioning
confidence: 99%
“…Studies in which fundamental frequency or formant frequencies were experimentally manipulated in voices have reported that increasing fundamental frequency or formant frequencies increased women's vocal attractiveness (Kandrik et al, 2016;Jones et al, 2010). By contrast, decreasing fundamental frequency or formant frequencies typically increased men's vocal attractiveness (Feinberg et al, 2005(Feinberg et al, , 2011Kandrik et al, 2016;Jones et al, 2010;Puts, 2005Puts, , 2006Tsantani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%